EXPLORING ASSOCIATIONS BETWEEN PARENTAL MILITARY SERVICE AND INSECURE ATTACHMENT IN MILITARY CHILDREN (Conferencea, 2023)
Military families experience contextual stressors like deployments, frequent relocations, family separations and reunions that necessitate changes in the family functioning, individual roles and responsibilities and its subsequent impact on the dynamics of a parent-child relationship. This paper analyzes the impact of military stressors on children using the “Attachment framework” as a developmental approach.